Emotional Intelligence Profiles and Mobbing in Nursing: The Mediating Role of Social Support and Sensitivity to Anxiety - María del Mar Molero Jurado; África Martos Martínez; Ana Belén Barragán Martín; María del Mar Simón Márquez; Nieves Fátima Oropesa Ruiz; Maria Sisto; María del Carmen Pérez-Fuentes; José Jesús Gázquez Linares (MDPI AG, 2021)
The prevalence of mobbing among nurses in various countries is around 17-20%. Some researchers have attempted to explain the success or failure of adaptation to the work environment and teamwork and to buffer the effects of psychological harassment in the workplace by incorporating emotional intelligence into the mobbing context. As its main objectives, this quantitative, observational, cross-sectional study analyzed the relationship between emotional intelligence and mobbing as perceived by nurses and sought to establish the mediating roles of other variables involved, such as social support and sensitivity to anxiety. The final sample consisted of 1357 Spanish, self-selected nurses aged 22-58 from multiple healthcare institutions. The questionnaires (Perceived Psychological Harassment Questionnaire, The Brief Emotional Intelligence Inventory, Brief Perceived Social Support Questionnaire, Anxiety Sensitivity Index-3) were implemented on a web platform, which enabled the participants to complete them online. Descriptive analyses and mediation models were estimated. Personal characteristics related to high sensitivity to anxiety and low emotional intelligence implied greater presence of mobbing at work. This mobbing may be buffered if the person perceives enough support from family, friends or significant others. Our results recommend reinforcing the social support network of nursing personnel to improve the work climate and training them in emotional intelligence in university and on-the-job programs.